Proposed Business Strategy And Its Implementation For Moslem Fashion Wear Ragazza - Pratama, Riski; Wandebori, Harimukti (The Indonesian Journal of Business Administration, 2014)
Abstract—Ragazza is a local brand in Indonesia, which serves customers with the products of Muslim women's clothing that is unique and also stylish. Along with the development of Muslim clothing industry as well as technology, the demand and revenue also increased for Ragazza. However, from the results of the analysis show that the performance of Ragazza not so good. Without a good strategy formulation causes Ragazza has unstable income and can’t meet the demand well. Strategy formulation process is done with the external and internal environment analysis to identify existing opportunities and threats that will be faced by Ragazza, as well as the strengths and weaknesses possessed by Ragazza that called SWOT analysis. Porter's Generic Competitive Strategy also performed to determine the focus of the strategy to be used. Blue Ocean Strategy is used to help Ragazza build an innovation strategy in this intense competition to make the competition irrelevant. Strategy Diamond helps in determining the strategy and the steps that necessary to compete in the market. Overall, this Muslim clothing market is an attractive market and has a promising growth in the future. Ragazza must take some appropriate action adapted to its capabilities. This implementation is done to improve the performance of Ragazza in order to capture the market and greater profits as well as improving the company's competitive position.Keywords: Muslim Clothing, Business Strategy, Blue Ocean Strategy, Strategy Diamond